Fungal pathogens associated with water hyacinth (Eichhornia crassipes Mart.) and their potential as biological control agents - Hassan, Iznee Rehanna (2021)
Water hyacinth, (Eichhornia crassipes Mart.), is an aquatic weed in South America, Europe and Asia. Water hyacinth has been identified as an aggressive invasive aquatic weed that could double up its population in two-weeks-time, making it detrimental once established. Water hyacinths form dense and thick mat across the water surface making it limited for sunlight to penetrate which made aquatic organisms deprived of sunlight. Water hyacinth also disrupts human activities such as in rice cultivation area, irrigation, water drainage, fishing for living and also recreational activities. A number of control methods for water hyacinth are currently implemented such as legislative, chemical and mechanical methods, but these methods are expensive, labor intensive and still give unsatisfactory result. Biological control method is a promising and eco-friendly method that is used to manage a number of pests, including invasive weeds. Several studies have been evaluating potential fungal pathogen and the effectiveness of fungal pathogens as mycoherbicides in suppressing water hyacinth populations, but the mycoherbicides developed are still in research stage. One of the aims of this study is to evaluate pathogenicity of fungal isolates obtained from diseased water hyacinth in Malaysia. 82 fungal isolates were obtained from five sampling locations, Sg. Limau (Kedah), Tasik Seri Serdang (Selangor), Kolam Seri Melor (Selangor), Tanjung Karang (Selangor) and Taman Tasik Cempaka Bangi (Selangor). Twenty-one fungal isolates grew full plate in 5 days of incubation and categorized as fast-growing fungi. Among the 21 fungal isolates, 12 isolates were found to be pathogenic to water hyacinth in detached leaf assay. Isolates derived from Sg. Limau and Tanjung Karang (D1 and D3) were found to be severely pathogenic (showing >80% incidence) to water hyacinth. Eight isolates that showed ≥ 50% disease incidence in detached leaf assay were subjected to whole plant bioassay for preliminary screening. All pathogenic isolates tested in whole plant bioassay showed significant differences from untreated water hyacinth except for isolate B2, Diaporthe drenthii sampled from Tasik Sri Serdang. Isolate D3, derived from Tanjung Karang, showed the highest percentage of disease incidence with means of 51.58% during the evaluation period. Both morphological and molecular analyses showed that the fungal isolates belonged to seven genera including Curvularia lunata, Epicoccum sorghinum, Diaporthe drenthii., Colletotrichum siamense, Xylaria sp., Myrothecium roridum and Mycoleptodiscus terrestris. This study provides an updated information on fungal isolates and identification of potential fungal pathogens associated with water hyacinth in Malaysia. Fungal isolates that were effective in suppressing water hyacinth, not pathogenic to paddy plants and not pathogenic to economically important crops were selected for assessment of disease severity. The selected isolates were Myrothecium roridum, Mycoleptodiscus terrestris and Xylaria sp. Myrothecium roridum was the most virulent and induced disease symptoms as lesions on leaves three days after inoculation. It also showed the highest disease severity (10.2%) and disease incidence (36.3%). This study developed Myrothecium roridum wettable powder formulation as mycoherbicide and evaluated the efficacy of the wettable powder formulation for controlling water hyacinth in glasshouse condition. Myrothecium roridum was selected as the active ingredient in wettable powder mycoherbicide formulation. The components of the wettable powder formulation in this study were active ingredient (40%), surfactants (10%), UV protectant (3.64%) and carrier (46.36%). Surfactants used were sodium lignosulfonate (Lig), sodium polyacrylate (PAAS), ELTESOL®SC (SC) and sodium naphthalene sulfonate (SNS). Surfactants used in the formulation did not inhibit the growth of M. roridum. Lig which took up the most percentage in the surfactant system had no inhibition towards M. roridum. Two different surfactant combination were incorporated in the formulations, Lig:PAAS:SC and Lig:PAAS:SNS with a ratio of 52:33:15. SC formulation had higher performance enhancement for individual physical tests but both formulations were graded as B. In vitro test showed viability of M. roridum growth for both SNS and SC formulation. SNS formulation on potato dextrose agar PDA media developed higher colony forming unit (cfu/mL), 8.1 ×103 cfu/mL and fast sporulation as compared to SC formulation with 3.6 ×103 cfu/mL. Disease severity in detached leaf assay when treated with SNS formulation was higher than non-inoculated treatment while SC formulation showed no difference with non-inoculated and SNS formulation. In glasshouse experiment, SNS formulation showed less control efficacy in controlling water hyacinth compared to non-formulated M. roridum for disease incidence (DI) and disease severity (DS) after 10 days of inoculation.